Analyzing micro parameters of diagonal stride in cross-country skiing using microsensors on snow - Rindal, O. M. H.; Gløersen, Ø.; Tjønnås, J. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Macro parameters of cross-country skiing, e.g. sub-technique classification, is thoroughly studied. However, detailed analysis of within-cycle movement of a sub technique, the micro parameters, have only been investigated on treadmills or with roller skis 1,2,3. We bring the lab-to-the-field and investigate the micro parameters of the diagonal stride in cross-country skiing while skiing on snow. We investigate the movement of the ski during the diagonal stride by mounting inertial measurement units (IMUs) on the skis. The first aim of this study was to automatically detect sub-phases of diagonal stride skiing on snow, specifically the sub-phases; glide, thrust and recovery. The second aim was to explore how these sub-phases are affected by changing from conventional- to running-style diagonal stride.